Copper foil with carrier, coreless support with wiring layer, and method for manufacturing printed circuit board
By introducing an intermediate layer and a peeling layer composed of Ti, Cr, Mo, Mn, W and Ni into the copper foil, the problems of unstable carrier peeling strength and insufficient peeling resistance are solved, and the coreless support is realized High-efficiency wiring layer formation and stable production of printed circuit boards.
Patent Information
- Application Number
- CN202010699030.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-09-05
- Filing Date
- 2017-02-21
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2037-02-21
AI Technical Summary
In the manufacturing process of the coreless support, the peel strength of the carrier is unstable, especially when a carbon layer is used as the peeling layer, it makes it difficult for the carrier to peel stably, and the peel resistance is insufficient in the photoresist development process. Influences the formation of wiring layers and chip installation.
The copper foil with a carrier is introduced into the intermediate layer consisting of Ti, Cr, Mo, Mn, W and Ni, and a peeling layer and an extremely thin copper layer are provided thereon. These layers are formed by a gas phase method such as sputtering method to improve the The peel resistance and mechanical peel strength of the developer.
In the photoresist development process, excellent peel resistance to the developer and stability of the mechanical peel strength of the carrier are achieved, the phenomenon of carrier detachment is avoided, and the formativity of the wiring pattern and the quality of the printed circuit board are improved.
Smart Images

Figure CN111787714B_ABST
Abstract
Description
[0001] The present application is a divisional application of an application filed on February 21, 2017, with application number 201780014211.2 and invention name “Copper foil with carrier, coreless support body with wiring layer and method for manufacturing printed circuit board”. Technical Field
[0002] The invention relates to a copper foil with a carrier, a coreless support body with a wiring layer, and a method for manufacturing a printed circuit board. Background Art
[0003] In recent years, in order to increase the mounting density of printed circuit boards and to reduce their size, the multilayering of printed circuit boards has been widely carried out. Such multilayer printed circuit boards are mostly used in mobile electronic devices for the purpose of weight reduction and miniaturization. In addition, the thickness of the interlayer insulating layer of the multilayer printed circuit board is required to be further reduced, and the circuit board is required to be further lightweight.
[0004] As a technology that meets such requirements, a method for manufacturing a multilayer printed circuit board using a coreless build-up method is adopted. The coreless build-up method refers to a method of alternately stacking (building up) insulating layers and wiring layers and forming a multilayer without using a so-called core substrate. In the coreless build-up method, it is proposed to use a copper foil with a carrier so that the peeling of the support body and the multilayer printed circuit board can be easily performed. For example, Patent Document 1 (Japanese Patent Publication No. 2005-101137) discloses a method for manufacturing a package substrate for mounting semiconductor elements, which includes: adhering an insulating resin layer to the carrier surface of the copper foil with a carrier to form a support body, forming a first wiring conductor on the extremely thin copper layer side of the copper foil with a carrier through processes such as photoresist processing, pattern copper plating, and resist removal, and then forming a build-up wiring layer, peeling off the support substrate with a carrier, and removing the extremely thin copper layer.
[0005] However, in order to miniaturize the embedded circuit shown in Patent Document 1, it is desired to make the thickness of the ultra-thin copper layer a copper foil with a carrier of less than 1 μm. Therefore, in order to reduce the thickness of the ultra-thin copper layer, a scheme of forming an ultra-thin copper layer by a vapor phase method is proposed. For example, Patent Document 2 (Japanese Patent Gazette No. 4726855) discloses a copper foil with a carrier sheet, which has a copper foil layer on the surface of the carrier sheet separated by a bonding interface layer, and discloses: The bonding interface layer is composed of two layers of a metal layer (carrier sheet side) / carbon layer (ultra-thin copper layer side) formed by a physical vapor deposition method, and the copper foil layer is obtained as follows: a first copper layer with a thickness of 10nm to 300nm is formed on the bonding interface layer by a physical vapor deposition method, and then a second copper layer is formed by an electrolytic method, thereby obtaining. In addition, Patent Document 2 records that the metal layer constituting the bonding interface layer can be a layer composed of any one of tantalum, niobium, zirconium, nickel, chromium, titanium, iron, silicon, molybdenum, vanadium, and tungsten.
[0006] In addition, Patent Document 3 (Japanese Patent No. 4072431) discloses a copper foil with a carrier, wherein a peeling layer which is a chromium layer and a layer which easily absorbs CO are sequentially laminated on the surface of the carrier foil. 2 A layer of light having a wavelength of gas laser oscillation, namely a diffusion-preventing layer, and an electroplated copper layer are disclosed, wherein the diffusion-preventing layer is a layer of a single metal formed by an element selected from the group consisting of nickel, cobalt, iron, molybdenum, tungsten, aluminum and phosphorus, or an alloy layer formed by two or more metals of elements selected from the group consisting of nickel, cobalt, iron, chromium, molybdenum, tungsten, copper, aluminum and phosphorus, or one or more metal oxide layers.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2005-101137
[0010] Patent Document 2: Japanese Patent No. 4726855
[0011] Patent Document 3: Japanese Patent No. 4072431
[0012] Patent Document 4: Japanese Patent Application Publication No. 2015-35551 Summary of the invention
[0013] However, in FO-WLP (Fan-Out Wafer Level Packaging) and FO-PLP (Fan-Out Panel Level Packaging), which are packaging technologies for printed circuit boards, the use of coreless build-up methods has also been studied. As one of such processes, there is a process called RDL-First (Redistribution Layer-First) method: a wiring layer and a built-up wiring layer as needed are formed on the surface of a coreless support body, and then the support body is peeled off as needed, and the chip is installed (for example, refer to patent document 4 (Japanese Patent Gazette No. 2015-35551)). According to this process, before the chip is installed, since the wiring layer on the surface of the coreless support body and the image inspection of each stacked wiring layer can be performed, the defective parts of each wiring layer can be avoided, and the chip can be installed only on the good part. As a result, in terms of avoiding unnecessary use of chips, the RDL-First method is economically advantageous compared to the process of stacking wiring layers in sequence on the surface of the chip, such as the Chip-First method. Here, in order to perform image inspection just after forming the wiring layer on the surface of the coreless support, after photoresist processing, electroplating and photoresist stripping are performed on the surface of the coreless support, and then the extremely thin copper layer existing between the wirings is rapidly etched as needed, the electronic components such as chips are mounted as needed, and then the stacking layer is formed. However, since heating is accompanied by the mounting of electronic components such as chips, there is a problem that warping is easily generated on the coreless support. In order to prevent this problem, it is considered to use materials with low coefficient of thermal expansion (CTE), i.e. glass, ceramics, low thermal expansion resins, etc. as carriers. However, when such low thermal expansion materials are used as carriers, there is a problem that the carrier becomes easy to peel off inadvertently. This problem is particularly significant when the peeling layer is a carbon layer. Therefore, it is considered to set a layer for improving adhesion between the peeling layer and the carrier, but at this time, the peeling strength of the carrier becomes unstable, and it is difficult to stably peel off the carrier when the coreless support is separated. In this way, there is the following problem: the desired mechanical peeling strength of the carrier cannot be stably obtained, that is, the mechanical peeling strength of the carrier is unstable. On the other hand, the copper foil with carrier is also expected to exhibit peeling resistance in the photoresist development step (for example, a step using a sodium carbonate aqueous solution as a developer) of forming a wiring layer on the surface of a coreless support.
[0014] The inventors of the present invention have obtained the following knowledge: by sandwiching an intermediate layer composed of a specified metal between the carrier and the peeling layer of the copper foil with a carrier, a copper foil with a carrier can be provided that exhibits excellent peeling resistance to a developer in a photoresist development process and can provide excellent stability for the mechanical peeling strength of the carrier.
[0015] Therefore, an object of the present invention is to provide a copper foil with a carrier which exhibits excellent peeling resistance to a developer in a photoresist development step and can provide excellent stability to the mechanical peeling strength of the carrier.
[0016] According to one aspect of the present invention, there is provided a copper foil with a carrier, comprising:
[0017] Carrier;
[0018] An intermediate layer provided on the carrier, wherein the surface of the carrier side contains 1.0 at % or more of at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni, and the surface opposite to the carrier side contains 30 at % or more of Cu;
[0019] a peeling layer disposed on the aforementioned intermediate layer; and,
[0020] The ultra-thin copper layer is disposed on the peeling layer.
[0021] According to another aspect of the present invention, there is provided a method for manufacturing a coreless support body with a wiring layer, comprising the following steps:
[0022] A step of preparing the copper foil with a carrier as a support;
[0023] A step of forming a photoresist layer in a predetermined pattern on the surface of the ultra-thin copper layer;
[0024] A step of forming an electroplated copper layer on the exposed surface of the ultra-thin copper layer;
[0025] The process of stripping the photoresist layer; and
[0026] A step of removing unnecessary portions of the ultra-thin copper layer by copper rapid etching to obtain a coreless support body having a wiring layer formed thereon.
[0027] According to another aspect of the present invention, there is provided a method for manufacturing a printed circuit board, comprising the following steps:
[0028] The step of manufacturing the coreless support body with wiring layer by the method described above;
[0029] A step of forming a build-up layer on the surface of the coreless support body with a wiring layer on which the wiring layer is formed, to produce a laminate with a build-up layer;
[0030] The step of separating the laminate with the build-up layer using the peeling layer to obtain a multilayer circuit board including the build-up layer; and
[0031] The process of processing the aforementioned multi-layer circuit board to obtain a printed circuit board. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic cross-sectional view showing one embodiment of the copper foil with a carrier of the present invention.
[0033] Figure 2 This is a schematic cross-sectional view showing another embodiment of the copper foil with a carrier of the present invention.
[0034] Figure 3 This is a process flow chart for explaining the method for manufacturing a coreless support body or a printed wiring board with a wiring layer of the present invention, and is a diagram showing the first half of the process (processes (a) to (c)).
[0035] Figure 4 The process flow chart for explaining the manufacturing method of the coreless support body or printed circuit board with wiring layer of the present invention is shown in FIG. Figure 3 A diagram of the processes (processes (d) to (f)).
[0036] Figure 5 The process flow chart for explaining the method for manufacturing a printed circuit board of the present invention is shown in FIG. Figure 4 A diagram of the processes (processes (g) to (i)). DETAILED DESCRIPTION
[0037] Copper foil with carrier
[0038] Figure 1 The copper foil with a carrier of the present invention is schematically shown in FIG. Figure 1 As shown, the copper foil with carrier 10 of the present invention includes a carrier 12, an intermediate layer 14, a peeling layer 16 and an ultra-thin copper layer 18 in this order. The intermediate layer 14 is a layer provided on the carrier 12, and the surface on the carrier 12 side contains 1.0 at% or more of at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni, and the surface on the opposite side to the carrier 12 contains 30 at% or more of Cu. The peeling layer 16 is a layer provided on the intermediate layer 14. The ultra-thin copper layer 18 is a layer provided on the peeling layer 16 and composed of copper. The copper foil with carrier 10 of the present invention may further include an anti-reflection layer 17 between the peeling layer 16 and the ultra-thin copper layer 18 as desired. In addition, the following structure may be formed: the above-mentioned various layers are provided in order in a manner that is vertically symmetrical on both sides of the carrier 12. The copper foil with carrier 10 is not particularly limited as long as a known layer structure is adopted except that it includes the above-mentioned intermediate layer 14 and the desired anti-reflection layer 17.
[0039] In this way, by sandwiching an intermediate layer 14 composed of a specified metal between the carrier 12 and the peeling layer 16 of the copper foil 10 with a carrier, excellent peeling resistance to the developer is exhibited in the photoresist development process, and excellent stability can be brought to the mechanical peeling strength of the carrier, and the detachment phenomenon of the intermediate layer generated when the coreless support or the carrier is peeled off can be prevented, thereby producing excellent wiring pattern formation. That is, the mechanism by which the intermediate layer 14 exerts the above-mentioned effect has not yet been determined, but it can be considered as follows. That is, although the copper on the surface of the intermediate layer 14 on the opposite side of the carrier 12 (i.e., the peeling layer 16 side) will give low adhesion to the material (e.g., carbon) constituting the peeling layer 16, which is conducive to stable peeling, on the other hand, the adhesion and peeling properties between carriers (e.g., glass, ceramics) may become unstable. In response to this problem, it is believed that by making the surface of the intermediate layer 14 on the carrier 12 side contain more than 1.0at% of at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni, it is convenient to provide excellent peeling stability and peeling resistance to the developer between the intermediate layer 14 and the carrier 12.
[0040] The material of the carrier 12 can be any of glass, ceramic, resin and metal. In addition, the form of the carrier 12 can be any of a sheet, a film, a plate and a foil. In addition, the carrier 12 can be a material obtained by stacking these sheets, films, plates and foils. For example, the carrier 12 can function in the form of a rigid support such as a glass plate, a ceramic plate, a metal plate, etc., or it can be a form that does not have rigidity such as a metal foil and a resin film. Preferred examples of the metal of the carrier 12 include copper, titanium, nickel, stainless steel, aluminum, etc. Preferred examples of ceramics include aluminum oxide, zirconium oxide, silicon nitride, aluminum nitride, and various fine ceramics. Preferred examples of resins include PET resin, PEN resin, aramid resin, polyimide resin, nylon resin, liquid crystal polymer, PEEK resin, polyimide resin, polyamide-imide resin, polyethersulfone resin, polyphenylene sulfide resin, PTFE resin, ETFE resin, etc. From the viewpoint of preventing the warping of the coreless support body caused by heating when mounting electronic components, a material with a coefficient of thermal expansion (CTE) lower than 25ppm / K (typically 1.0 to 23ppm / K) is more preferred. Examples of such materials include the various resins mentioned above (especially low thermal expansion resins such as polyimide resins and liquid crystal polymers), glass, and ceramics. In addition, from the viewpoint of operability and ensuring flatness during chip mounting, the carrier 12 preferably has a Vickers hardness of 100HV or more, more preferably 150 to 2500HV. As a material that satisfies these characteristics, the carrier 12 is preferably composed of a resin film, glass or ceramics, more preferably glass or ceramics, and particularly preferably glass. For example, a glass sheet. When glass is used as the carrier 12, there are the following advantages: light weight, low coefficient of thermal expansion, high insulation, and the surface of the ultra-thin copper layer 18 can be made extremely smooth due to its rigidity and flat surface. In addition, when the carrier is glass, there are the following advantages: when the wiring layer on the surface of the coreless support is formed and the image is inspected, the contrast between the visibility and the copper plating layer is excellent; when the electronic components are mounted, it has a favorable surface flatness (coplanarity); it has chemical resistance in the desmearing and various plating processes in the printed circuit board manufacturing process; when the laminated body with the laminated layer described later is separated, a chemical separation method can be used. As preferred examples of glass constituting the carrier 12, quartz glass, borosilicate glass, alkali-free glass, soda-lime glass, amino silicate glass, and combinations thereof can be cited, and alkali-free glass is particularly preferred. Alkali-free glass is glass that contains silicon dioxide, aluminum oxide, boron oxide, and alkaline earth metal oxides such as calcium oxide and barium oxide as main components, and further contains boric acid, and does not substantially contain alkali metals. This alkali-free glass has a low and stable thermal expansion coefficient in the range of 3 to 5 ppm / K in a wide temperature range of 0°C to 350°C, so when a semiconductor chip as an electronic component is mounted, there is an advantage that the warping of the glass can be minimized.The thickness of the carrier is preferably 100 to 2000 μm, more preferably 300 to 1800 μm, and further preferably 400 to 1100 μm. When the thickness is within this range, appropriate strength can be ensured without causing trouble in handling, and the printed circuit board can be made thinner and warping generated when electronic components are mounted can be reduced.
[0041] The surface on the side of the intermediate layer 14 of the carrier 12 preferably has an arithmetic mean roughness Ra of 0.1 to 70 nm, more preferably 0.5 to 60 nm, further preferably 1.0 to 50 nm, particularly preferably 1.5 to 40 nm, and most preferably 2.0 to 30 nm, as measured in accordance with JIS B 0601-2001. As such, the smaller the arithmetic mean roughness, the lower the desired arithmetic mean roughness Ra can be given to the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 (the outer surface of the ultra-thin copper layer 18), and thus, in the printed wiring board manufactured using the copper foil 10 with a carrier, it is suitable for forming a wiring pattern with a high degree of miniaturization to a line / space (L / S) of 13 μm or less / 13 μm or less (e.g., 12 μm / 12 μm to 2 μm / 2 μm).
[0042] From the perspective of ensuring the adhesion between the carrier 12 and the intermediate layer 14, the surface of the intermediate layer 14 on the carrier 12 side is a metal containing at least one metal (hereinafter referred to as metal M) selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni. The content of metal M in the surface of the intermediate layer 14 on the carrier 12 side is preferably 1.0 atomic % or more, more preferably 3.0 atomic % or more, and further preferably 4.0 atomic % or more. The metal can be a pure metal or an alloy. Therefore, the upper limit of the content of the above-mentioned metal M is not particularly limited and can be 100 atomic %. On the other hand, the surface of the intermediate layer 14 on the opposite side of the carrier 12 is a metal containing Cu. From the perspective of maintaining easy peelability with the peeling layer, the Cu content in the surface of the intermediate layer 14 on the opposite side of the carrier 12 (i.e., the peeling layer 16 side) is preferably 30 atomic % or more, more preferably 40 atomic % or more, and further preferably 50 atomic % or more. The upper limit of the above-mentioned Cu content is not particularly limited and can be 100 atomic %.
[0043] The thickness of the intermediate layer 14 is preferably 5 to 1000 nm, more preferably 10 to 800 nm, further preferably 12 to 500 nm, and particularly preferably 15 to 400 nm. The thickness is a value measured by analyzing a layer cross section using an energy dispersive X-ray analyzer (TEM-EDX) of a transmission electron microscope.
[0044] The middle layer 14 is as Figure 1 As shown, it can be composed of one layer, and can be Figure 2 As shown, it is a structure of two or more layers.
[0045] According to a preferred embodiment of the present invention, the intermediate layer 14 is as follows Figure 2 As shown, it includes a close-fitting metal layer 14a and a stripping auxiliary layer 14b. The close-fitting metal layer 14a is a layer arranged on the carrier 12 and composed of at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni. The stripping auxiliary layer 14b is a layer arranged on the close-fitting metal layer 14a and composed of copper. In this way, by combining the close-fitting metal layer 14a composed of a specified metal and the stripping auxiliary layer 14b composed of copper and sequentially sandwiching them between the carrier 12 and the stripping layer 16 of the copper foil 10 with a carrier, it is possible to exhibit excellent stripping resistance to the developer in the photoresist development process, and can bring excellent stability to the mechanical stripping strength of the carrier. That is, the mechanism by which the combination of the close-fitting metal layer 14a and the stripping auxiliary layer 14b exerts the above-mentioned effect has not yet been determined, but can be considered as follows. That is, although the copper constituting the peeling auxiliary layer 14b will impart low adhesion to the material constituting the peeling layer 16 (such as carbon), which is conducive to stable peeling, on the other hand, the adhesion and peeling properties between the carrier (such as glass, ceramic) may become unstable. In response to this problem, it is believed that by sandwiching a bonding metal layer 14a between the peeling auxiliary layer 14b and the carrier 12, it is convenient to impart excellent peeling stability and peeling resistance to the developer between the peeling auxiliary layer 14b and the carrier 12, and to facilitate imparting excellent wiring pattern forming properties by preventing the detachment phenomenon of the intermediate layer generated when peeling the coreless support or the carrier.
[0046] From the aspect of ensuring the adhesion between the carrier 12 and the stripping auxiliary layer 14b, the close metal layer 14a is preferably a layer composed of at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni, which can be a pure metal or an alloy. Among them, from the aspect of ensuring the adhesion between the carrier 12 and the close metal layer 14a and the stripping auxiliary layer 14b, significantly preventing the stripping of the extremely thin copper layer in the formation process of the coreless support wiring layer described later, and the stripping of the close metal layer 14a and the stripping auxiliary layer 14b as the metal on the carrier side generated when the coreless support is stripped, the close metal layer 14a is most preferably composed of Ti. The metal constituting the close metal layer 14a may contain inevitable impurities derived from raw material components, film forming processes, etc. In addition, although there is no particular restriction, when the close metal layer 14a is exposed to the atmosphere after film formation, the presence of oxygen mixed therein is allowed. The close metal layer 14a is preferably a layer formed by a gas phase method such as sputtering. From the aspect of improving the uniformity of the film thickness distribution, it is particularly preferred that the close-fitting metal layer 14a is a layer formed by a magnetron sputtering method using a metal target. The thickness of the close-fitting metal layer 13 is preferably 5 to 500 nm, more preferably 10 to 300 nm, further preferably 18 to 200 nm, and particularly preferably 20 to 100 nm. The thickness is a value measured by analyzing the layer cross section with an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope.
[0047] The stripping auxiliary layer 14b is a layer composed of copper. The copper constituting the stripping auxiliary layer 14b may contain inevitable impurities derived from raw material components, film forming processes, etc. The stripping auxiliary layer 14b may contain at least one metal selected from the group consisting of Si, Al, Ni, Mn, Mg, Nd, Nb, Ag, Zn, Sn, Bi and Fe within the range that does not damage the stripping property of the carrier. In the above case, the stripping auxiliary layer can be said to be a layer mainly containing copper. From the above aspect, the content of the Cu element in the stripping auxiliary layer 14b is preferably 50 to 100 atomic%, more preferably 60 to 100 atomic%, further preferably 70 to 100 atomic%, particularly preferably 80 to 100 atomic%, and most preferably 90 to 100 atomic%. In addition, when the stripping auxiliary layer 14b is exposed to the atmosphere before and after film formation, the presence of oxygen mixed therein is allowed. Although there is no particular restriction, it is desired that the adhesion metal layer 14a and the stripping auxiliary layer 14b are continuously formed without being exposed to the atmosphere. The peeling auxiliary layer 14b is preferably a layer formed by a gas phase method such as sputtering. From the aspect of being able to improve the uniformity of the film thickness distribution, it is particularly preferred that the peeling auxiliary layer 14b is a layer formed by a magnetron sputtering method using a copper target. The thickness of the peeling auxiliary layer 14b is preferably 5 to 500 nm, more preferably 10 to 400 nm, further preferably 15 to 300 nm, and particularly preferably 20 to 200 nm. The thickness is a value measured by analyzing the layer cross section using an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope.
[0048] It should be noted that another interlayer may exist between the adhesion metal layer 14a and the peeling auxiliary layer 14b. Examples of the constituent material of the interlayer include alloys of Cu and at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni.
[0049] According to another preferred embodiment of the present invention, Figure 1As shown, the intermediate layer 14 can be an intermediate alloy layer. That is, the intermediate layer 14 can be set to be composed of one layer. The intermediate layer 14 as an intermediate alloy layer is preferably composed of a copper alloy containing at least one metal (hereinafter referred to as metal M) selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni, which is 1.0 at% or more and a Cu content of 30 at% or more. That is, from the perspective of ensuring the adhesion between the carrier 12 and the intermediate layer 14 and taking into account the easy peeling of the peeling layer 16, the metal constituting the intermediate alloy layer is preferably a copper alloy of metal M and Cu. Among them, an alloy containing at least one metal selected from the group consisting of Ti, Mo, and Mn and Cu is more preferred. The content of metal M in the intermediate alloy layer is preferably 1.0 atomic % or more, more preferably 3.0 atomic % or more, and further preferably 5.0 atomic % or more. Although there is no particular upper limit on the content of metal M in the intermediate alloy layer, the content of metal M is preferably 30 atomic % or less, and more preferably 20 atomic % or less. The Cu content in the intermediate alloy layer is preferably 30 atomic % or more, more preferably 40 atomic % or more, and further preferably 50 atomic % or more. Although there is no particular limit on the upper limit of the Cu content in the intermediate alloy layer, the Cu content is preferably 99.5 atomic % or less, more preferably 97.0 atomic % or less, and further preferably 96.0 atomic % or less. The intermediate alloy layer is preferably a layer formed by a gas phase method such as sputtering. From the perspective of improving the uniformity of the film thickness distribution, the intermediate alloy layer is particularly preferably a layer formed by a magnetron sputtering method using a copper alloy target. The thickness of the intermediate alloy layer is preferably 5 to 500 nm, more preferably 10 to 400 nm, further preferably 15 to 300 nm, and particularly preferably 20 to 200 nm. The thickness is a value measured by analyzing the layer cross section using an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope. It should be noted that other interlayers may be present inside the intermediate alloy layer. Examples of the constituent material of the interlayer include alloys of Cu and at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W, and Ni.
[0050] The peeling layer 16 is a layer that can realize the peeling of the carrier 12 (which is accompanied by the intermediate layer 14). The peeling layer 16 can be any of an organic peeling layer and an inorganic peeling layer. Examples of organic components used in the organic peeling layer include nitrogen-containing organic compounds, sulfur-containing organic compounds, carboxylic acids, etc. Examples of nitrogen-containing organic compounds include triazole compounds, imidazole compounds, etc. On the other hand, examples of inorganic components used in the inorganic peeling layer include metal oxides of at least one of Ni, Mo, Co, Cr, Fe, Ti, W, P, and Zn, carbon layers, etc. Among them, from the aspects of easy peeling and film formation, it is particularly preferred that the peeling layer 16 is a layer mainly composed of carbon, more preferably a layer mainly composed of carbon or hydrocarbons, and further preferably formed of amorphous carbon belonging to a hard carbon film. In the above case, the carbon concentration of the peeling layer 16 (i.e., the carbon layer) measured by XPS is preferably 60 atomic % or more, more preferably 70 atomic % or more, further preferably 80 atomic % or more, and particularly preferably 85 atomic % or more. The upper limit of the carbon concentration is not particularly limited and may be 100 atomic %, but 98 atomic % or less is realistic. The peeling layer 16 (especially the carbon layer) may contain inevitable impurities (such as oxygen, carbon, hydrogen, etc. from the surrounding environment such as the atmosphere). In addition, metal atoms may be mixed into the peeling layer 16 (especially the carbon layer) due to the film forming method of the anti-reflection layer 17 or the ultra-thin copper layer. The mutual diffusion and reactivity between carbon and the carrier are small, and even if subjected to press processing at a temperature exceeding 300°C, the formation of metal bonds caused by high-temperature heating between the copper foil layer and the bonding interface can be prevented, and the carrier can be easily peeled and removed. From the perspective of suppressing excessive impurities in amorphous carbon and the continuous productivity of the film formation of the aforementioned intermediate layer 14, it is preferred that the peeling layer 16 is also a layer formed by a gas phase method such as sputtering. The thickness of the peeling layer 16 is preferably 1 to 20 nm, and more preferably 1 to 10 nm. The thickness is a value measured by analyzing the layer cross section using an energy dispersive X-ray spectrometer (TEM-EDX) of a transmission electron microscope.
[0051] The anti-reflection layer 17 set as desired is a layer having the function of preventing light reflection. Preferably, the anti-reflection layer 17 is composed of at least one metal selected from the group consisting of Cr, W, Ta, Ti, Ni and Mo, and at least the surface on the side of the ultra-thin copper layer 18 is an aggregate of metal particles. In this case, the anti-reflection layer 17 can be a layer structure composed of an aggregate of metal particles as a whole, or a multilayer structure including a layer formed by an aggregate of metal particles and a non-granular layer located below it. The aggregate of metal particles on the surface of the ultra-thin copper layer 18 side constituting the anti-reflection layer 17 presents a desired dark color due to its metallic material and granular morphology, and the dark color brings a desired visual contrast with the wiring layer composed of copper, and as a result, the visibility in image inspection (such as automatic image inspection (AOI)) is improved. That is, the surface of the anti-reflection layer 17 generates diffuse reflection of light due to the convex shape of the metal particles and is recognized as black. Moreover, the anti-reflection layer 17 has appropriate adhesion and peelability with the peeling layer 16, and excellent adhesion with the ultra-thin copper layer 18, and excellent peeling resistance to the developer when the photoresist layer is formed. From the viewpoint of the above-mentioned contrast and improved visibility, the glossiness Gs (60°) of the surface of the ultra-thin copper layer 18 side of the anti-reflection layer 17 is preferably 500 or less, more preferably 450 or less, further preferably 400 or less, particularly preferably 350 or less, and most preferably 300 or less. The lower limit of the glossiness Gs (60°) is preferably as low as possible, so it is not particularly limited, but the glossiness Gs (60°) of the surface of the ultra-thin copper layer 18 side of the anti-reflection layer 17 is actually 100 or more, more realistically 150 or more. It should be noted that the specular glossiness Gs (60°) of the roughened particles based on image analysis can be measured using a commercially available gloss meter in accordance with JIS Z 8741-1997 (Specular glossiness-measurement method).
[0052] More specifically, an anti-reflection layer 17 composed of a predetermined metal and having a surface of at least the ultra-thin copper layer 18 side as an aggregate of metal particles is sandwiched between the release layer 16 and the ultra-thin copper layer 18, thereby providing a copper foil with a carrier having the following characteristics: 1) when the wiring layer is formed on the surface of the coreless support, the anti-reflection layer exhibits excellent chemical resistance to a copper rapid etching solution, and 2) during image inspection after copper rapid etching (e.g., automatic image inspection (AOI)), the wiring layer is excellently visible by utilizing the contrast with the anti-reflection layer. That is, with respect to the above 1), at least one metal selected from Cr, W, Ta, Ti, Ni and Mo constituting the anti-reflection layer 17 has the property of being insoluble in a copper rapid etching solution, and as a result, can exhibit excellent chemical resistance to a copper rapid etching solution. In addition, regarding the above 2), the aggregate of metal particles on the surface of at least the extremely thin copper layer 18 side constituting the anti-reflection layer 17 presents a desired dark color due to the material and granular form of the metal, and the dark color brings a desired visual contrast with the wiring layer composed of copper, resulting in improved recognition in image inspection (such as automatic image inspection (AOI)). In addition, when the copper foil with a carrier of this method is used to manufacture a coreless support or a printed circuit board with a wiring layer, 3) when the anti-reflection layer is removed by rapid etching, the corrosion of the wiring layer exposed under the anti-reflection layer can be significantly suppressed. That is, as an etching solution for rapid etching of at least one metal selected from Cr, W, Ta, Ti, Ni and Mo constituting the anti-reflection layer 17, a highly selective etching solution can be used, and as a result, the dissolution of copper constituting the wiring layer caused by the etching solution can be suppressed or avoided.
[0053] In addition, from the viewpoint of improving contrast and visibility, and improving uniformity of rapid etching, the surface of the ultra-thin copper layer 18 side of the anti-reflection layer 17 is preferably composed of an aggregate of metal particles having a projected area circle equivalent diameter of 10 to 100 nm determined by SEM image analysis, more preferably 25 to 100 nm, and further preferably 65 to 95 nm. The above-mentioned projected area circle equivalent diameter can be measured as follows: the surface of the anti-reflection layer 17 is photographed by a scanning electron microscope at a predetermined magnification (e.g., 50,000 times), and the image analysis of the obtained SEM image is performed. Specifically, it is preferred to use commercially available image analysis type particle size distribution software and adopt the arithmetic mean of the projected area circle equivalent diameter.
[0054] The anti-reflection layer 17 is composed of at least one metal selected from Cr, W, Ta, Ti, Ni and Mo, preferably at least one metal selected from Ta, Ti, Ni and Mo, more preferably at least one metal selected from Ti, Ni and Mo, and most preferably Ti. These metals may be pure metals or alloys. In any case, these metals are not essentially oxidized (not essentially metal oxides) and will present a desired dark color that improves the visual contrast with Cu, so it is preferred. Specifically, the oxygen content of the anti-reflection layer 17 is preferably 0 to 15 atomic%, more preferably 0 to 13 atomic%, and further preferably 1 to 10 atomic%. In any case, the above metals have the property of being insoluble in copper rapid etching liquid, and as a result, they can present excellent chemical resistance to copper rapid etching liquid. The thickness of the anti-reflection layer 17 is preferably 1 to 500 nm, more preferably 10 to 300 nm, further preferably 20 to 200 nm, and particularly preferably 30 to 150 nm.
[0055] The ultra-thin copper layer 18 can be manufactured by any method, for example, it can be a copper foil formed by a wet film forming method such as chemical copper plating and electroplating, a physical vapor film forming method such as sputtering and vacuum evaporation, a chemical vapor film forming method, or a combination thereof. From the perspective of being easy to cope with fine pitch based on ultra-thinning, a particularly preferred ultra-thin copper layer is a copper layer formed by a vapor phase method such as sputtering and vacuum evaporation, and the most preferred is a copper layer manufactured by sputtering. In addition, when the ultra-thin copper layer is preferably a copper layer without roughening, as long as it does not cause obstacles to the formation of wiring patterns during the manufacture of printed circuit boards, secondary roughening can also be produced by pre-roughening, soft etching, cleaning, and oxidation-reduction treatment. The thickness of the ultra-thin copper layer 18 is not particularly limited. In order to cope with the above-mentioned fine pitch, it is preferably 50 to 3000nm, more preferably 70 to 2500nm, further preferably 80 to 2000nm, particularly preferably 90 to 1500nm, particularly preferably 120 to 1000nm, and most preferably 150 to 500nm. From the viewpoint of the in-plane uniformity of the film thickness and the productivity in the form of a sheet or a roll, the ultra-thin copper layer having a thickness within such a range is preferably produced by a sputtering method.
[0056] The surface of the ultra-thin copper layer 18 on the opposite side to the release layer 16 (the outer surface of the ultra-thin copper layer 18) preferably has an arithmetic mean roughness Ra of 1.0 to 100 nm, more preferably 2.0 to 40 nm, further preferably 3.0 to 35 nm, particularly preferably 4.0 to 30 nm, and most preferably 5.0 to 15 nm, as measured in accordance with JIS B 0601-2001. The smaller the arithmetic mean roughness, the more suitable it is for forming a highly micronized wiring pattern to a degree such as line / space (L / S) of 13 μm or less / 13 μm or less (e.g., 12 μm / 12 μm to 2 μm / 2 μm) in a printed wiring board manufactured using the copper foil 10 with a carrier.
[0057] The ultra-thin copper layer 18, the desired anti-reflection layer 17, the desired intermediate layer 14 (e.g., the adhesion metal layer 14a and / or the peeling auxiliary layer 14b, or the intermediate alloy layer), and the desired peeling layer 16 (i.e., at least the ultra-thin copper layer 18, e.g., the ultra-thin copper layer 18 and the anti-reflection layer 17) preferably extend to the end face of the carrier 12 and cover the end face. That is, it is preferred that not only the surface of the carrier 12 but also the end face is covered by at least the ultra-thin copper layer 18. Since the end face is also covered, in addition to preventing the intrusion of the chemical solution in the printed circuit board process into the carrier 12, it is possible to effectively prevent the cutting caused by peeling at the side end when the coreless support is handled (e.g., during roller conveyance), that is, the chipping of the coating (i.e., the ultra-thin copper layer 18 and the anti-reflection layer 17 when present) on the peeling layer 16. The film thickness of the adhesion metal layer 14a at the end surface of the carrier 12 (the thickness in the perpendicular direction relative to the end surface, hereinafter referred to as "end surface thickness") is preferably 2 to 350 nm, more preferably 3 to 220 nm, further preferably 5 to 150 nm, and particularly preferably 6 to 70 nm. The end surface thickness of the peeling auxiliary layer 14b is preferably 2 to 350 nm, more preferably 3 to 220 nm, further preferably 5 to 150 nm, and particularly preferably 6 to 70 nm. The end surface thickness of the intermediate layer 14 as the intermediate alloy layer is preferably 2 to 350 nm, more preferably 3 to 220 nm, further preferably 5 to 150 nm, and particularly preferably 6 to 70 nm. The end surface thickness of the peeling layer 16 is preferably 0 to 15 nm, more preferably 0 to 3 nm, further preferably 0 to 1 nm, particularly preferably 0 to 0.5 nm, and most preferably 0 nm. That is, it is most preferred that the peeling layer 16 is not formed on the end surface of the carrier. The end face thickness of the anti-reflection layer 17 is preferably 2 to 350 nm, more preferably 3 to 220 nm, further preferably 5 to 150 nm, and particularly preferably 6 to 70 nm. The end face thickness of the ultra-thin copper layer 18 is preferably 15 to 2800 nm, more preferably 20 to 1800 nm, further preferably 25 to 1400 nm, particularly preferably 27 to 1350 nm, particularly preferably 35 to 700 nm, and most preferably 45 to 350 nm. In addition, the coverage area in the end face of the carrier 12 preferably covers an area of more than 0.1 mm from the surface of the carrier 12 in the thickness direction (i.e., in a direction perpendicular to the carrier surface), more preferably an area of more than 0.2 mm, and further preferably the entire end face of the carrier 12. In this way, the gap in the coating at the side end of the coreless support and the intrusion of the chemical solution to the carrier in the printed circuit board process can be effectively prevented.
[0058] Method for producing copper foil with carrier
[0059] The copper foil with a carrier 10 of the present invention can be manufactured as follows: prepare the above-mentioned carrier 12, and form an intermediate layer 14 (for example, two layers of a close metal layer 14a and a peeling auxiliary layer 14b, or one layer of an intermediate alloy layer) on the carrier 12, a peeling layer 16, an anti-reflection layer 17 as desired, and an ultra-thin copper layer 18. From the perspective of easy response to fine pitch based on ultra-thinning, the formation of each layer of the intermediate layer 14, the peeling layer 16, the anti-reflection layer 17 (if present) and the ultra-thin copper layer 18 is preferably performed by a vapor phase method. As examples of the vapor phase method, sputtering, vacuum evaporation and ion plating can be cited. From the perspective of being able to control the film thickness in a wide range such as 0.05nm to 5000nm, and being able to ensure the uniformity of the film thickness in a wide range or even over the entire area, the sputtering method is most preferred. In particular, all the layers of the intermediate layer 14, the peeling layer 16, the anti-reflection layer 17 (if present) and the ultra-thin copper layer 18 are formed by the sputtering method, so that the manufacturing efficiency becomes particularly high. Film formation using a vapor phase method is not particularly limited as long as it is performed using a known vapor phase film forming device according to known conditions. For example, in the case of sputtering, the sputtering method can be various known methods such as magnetron sputtering, bipolar sputtering, and opposing target sputtering. From the perspective of fast film forming speed and high productivity, magnetron sputtering is preferred. Sputtering can be performed under any power supply of DC (direct current) and RF (high frequency). In addition, although a plate-type target with a widely known target shape can also be used, from the perspective of target use efficiency, it is desirable to use a cylindrical target. Below, the film formation using a vapor phase method (preferably sputtering) of each layer of the intermediate layer 14 (such as the 2 layers of the close-fitting metal layer 14a and the stripping auxiliary layer 14b, or the 1 layer of the intermediate alloy layer), the stripping layer 16, the anti-reflection layer 17 (when present) and the ultra-thin copper layer 18 is described.
[0060] From the perspective of improving the uniformity of film thickness distribution, the film formation of the close-fitting metal layer 14a using the gas phase method is preferably carried out by magnetron sputtering in a non-oxidizing atmosphere using a target composed of at least one metal selected from the group consisting of Ti, Cr and Ni. The purity of the target is preferably 99.9% or more. As the gas used in sputtering, it is preferred to use an inert gas such as argon. The flow rate of argon is not particularly limited as long as it is appropriately determined according to the size of the sputtering chamber and the film forming conditions. In addition, from the perspective of continuous film formation without abnormal discharge or poor plasma irradiation and other operational problems, the pressure during film formation is preferably in the range of 0.1 to 20 Pa. This pressure range can be set by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of the film thickness and productivity of the film formation, the sputtering power can be 0.05 to 10.0 W / cm per unit area of the target. 2 It can be appropriately set within the range of
[0061] From the perspective of improving the uniformity of film thickness distribution, the film formation of the stripping auxiliary layer 14b using the vapor phase method is preferably carried out by magnetron sputtering using a copper target in a non-oxidizing atmosphere. The purity of the copper target is preferably 99.9% or more. As the gas used in sputtering, an inert gas such as argon is preferably used. The flow rate of argon is not particularly limited as long as it is appropriately determined according to the sputtering chamber size and film forming conditions. In addition, from the perspective of continuous film formation without abnormal discharge or poor plasma irradiation and other operational problems, the pressure during film formation is preferably in the range of 0.1 to 20 Pa. This pressure range can be set by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of film thickness and productivity of the film formation, the sputtering power can be 0.05 to 10.0 W / cm per unit area of the target. 2 It can be appropriately set within the range of
[0062] When the intermediate layer 14 is an intermediate alloy layer, from the perspective of improving the uniformity of the film thickness distribution, the intermediate layer 14 is preferably formed by magnetron sputtering in a non-oxidizing atmosphere using an alloy target of at least one metal M selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni and Cu. The purity of the copper target is preferably 99.9% or more. As the gas used in sputtering, an inert gas such as argon is preferably used. The flow rate of argon is not particularly limited as long as it is appropriately determined according to the sputtering chamber size and film forming conditions. In addition, from the perspective of continuous film formation without abnormal discharge or poor plasma irradiation and other operational problems, the pressure during film formation is preferably in the range of 0.1 to 20 Pa. This pressure range can be set by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of the film thickness and productivity of the film formation, the sputtering power can be 0.05 to 10.0 W / cm per unit area of the target. 2 It can be appropriately set within the range of
[0063] The film formation of the peeling layer 16 by a gas phase method (preferably a sputtering method) is preferably carried out using a carbon target in an inert atmosphere such as argon. The carbon target is preferably composed of graphite, but may contain unavoidable impurities (such as oxygen and carbon from the surrounding environment such as the atmosphere). The purity of the carbon target is preferably above 99.99%, and more preferably above 99.999%. In addition, from the viewpoint of continuous film formation without abnormal discharge or poor operation such as poor plasma irradiation, the pressure during film formation is preferably in the range of 0.1 to 2.0 Pa. This pressure range can be set by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of the film thickness and productivity of the film formation, the sputtering power can be 0.05 to 10.0 W / cm per unit area of the target. 2 It can be appropriately set within the range of
[0064] The film formation of the anti-reflection layer 17 is preferably carried out by magnetron sputtering using a target composed of at least one metal selected from the group consisting of Cr, W, Ta, Ti, Ni and Mo. The purity of the target is preferably 99.9% or more. The film formation of the anti-reflection layer 17 by magnetron sputtering is particularly preferably carried out in an atmosphere of an inert gas such as argon at a pressure of 1 to 20 Pa. The sputtering pressure is more preferably 2 to 18 Pa, and further preferably 3 to 15 Pa. Such a sputtering pressure is significantly higher than the sputtering pressure commonly used, thereby allowing a collection of metal particles of the desired shape to be uniformly formed in the plane without essentially oxidizing the surface of the anti-reflection layer 17. According to the above-mentioned sputtering conditions, the desired projected area circle equivalent diameter and the desired glossiness Gs (60°) can also be achieved. In addition, there are the following advantages: there is no abnormal discharge, poor plasma irradiation and other operational problems, and continuous film formation is possible. It should be noted that the control of the above pressure range can be carried out by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. The flow rate of argon gas is not particularly limited as long as it is appropriately determined according to the sputtering chamber size and film forming conditions. In addition, considering the uniformity of film thickness and productivity of the film, the sputtering power can be 1.0 to 15.0 W / cm per unit area of the target. 2 In addition, from the perspective of easily obtaining stable film properties (such as film resistance and crystal size), it is preferred to keep the carrier temperature constant during film formation. The carrier temperature during film formation is preferably adjusted within the range of 25 to 300°C, more preferably within the range of 40 to 200°C, and further preferably within the range of 50 to 150°C.
[0065] The film formation of the ultra-thin copper layer 18 by the vapor phase method (preferably the sputtering method) is preferably carried out using a copper target in an inert atmosphere such as argon. The copper target is preferably composed of metallic copper and may contain inevitable impurities. The purity of the copper target is preferably 99.9% or more, more preferably 99.99%, and further preferably 99.999% or more. In order to avoid the temperature rise during the vapor phase film formation of the ultra-thin copper layer 18, a cooling mechanism of the mounting table can be provided during sputtering. In addition, from the perspective of stable film formation without abnormal discharge or poor plasma irradiation and other operational problems, the pressure during film formation is preferably in the range of 0.1 to 2.0 Pa. This pressure range can be set by adjusting the film forming power and the flow rate of argon gas according to the device structure, capacity, exhaust capacity of the vacuum pump, rated capacity of the film forming power supply, etc. In addition, considering the uniformity of the film thickness and productivity of the film formation, the sputtering power can be 0.05 to 10.0 W / cm per unit area of the target. 2 It can be appropriately set within the range of
[0066] It should be noted that the formation of the intermediate layer 14, the peeling layer 16, the anti-reflection layer 17 and / or the ultra-thin copper layer 18 on the end face of the carrier 12 can be easily implemented as follows: in the above-mentioned sputtering method, the film is formed in a state where the end face of the carrier 12 is exposed on the mounting table. At this time, typically, the film is formed on the end face of the carrier 12 with a thickness of 20% to 70% of the thickness of the surface layer of the carrier 12 (end face thickness). On the other hand, when the peeling layer 16 is formed, when the end face is formed with an extremely thin thickness, it is preferable to shield the side end of the carrier 12 during sputtering. As examples of the shielding method, shielding using masking tape and shielding using a masking plate can be cited.
[0067] Coreless support laminate
[0068] The copper foil with a carrier of the present invention can be provided in the form of a laminated board for a coreless support. That is, according to a preferred embodiment of the present invention, there is provided: a laminated board for a coreless support having the above-mentioned copper foil with a carrier. As the form of the laminated board for a coreless support, the following two forms can be cited. (i) The first form of the laminated board for a coreless support is the form of the copper foil with a carrier itself. That is, it is the form of the copper foil 10 with a carrier itself, in which an intermediate layer 14 / peeling layer 16 / anti-reflection layer 17 as required / ultra-thin copper layer 18 are sequentially stacked on at least one side of the carrier 12, including: the form in which an intermediate layer 14 / peeling layer 16 / anti-reflection layer 17 as required / ultra-thin copper layer 18 are sequentially stacked on both sides of the carrier. In any case, when the carrier 12 is a glass plate, a metal plate, etc., this form is established when the carrier monomer has rigidity and can function as a support. For example, when glass is used as the carrier 12, there are advantages such as light weight, low thermal expansion coefficient, rigidity and flat surface, so the surface of the ultra-thin copper layer 18 can be made extremely smooth. (ii) The second form of the laminated plate for a coreless support is a form in which an adhesive layer is provided on the side of the carrier 12 opposite to the peeling layer 16 (i.e., the outer surface of the carrier 12). This form is considered when the carrier 12 is composed of a non-rigid material such as a metal foil or a resin film. In the above case, examples of the adhesive layer include a resin layer, a fiber-reinforced prepreg (glass, etc.), etc. For example, a layer structure of ultra-thin copper layer 18 / anti-reflection layer 17 as required / peeling layer 16 / intermediate layer 14 / carrier 12 / adhesive layer (not shown) / carrier 12 / intermediate layer 14 / peeling layer 16 / anti-reflection layer 17 as required / ultra-thin copper layer 18 can also be used. It should be noted that the intermediate layer 14 may have two layers of the adhesion metal layer 14 a and the peeling auxiliary layer 14 b in order from the support 12 side, or may be a single intermediate alloy layer, as described above.
[0069] Method for manufacturing coreless support body with wiring layer
[0070] The copper foil with a carrier of the present invention can be used to manufacture a coreless support body with a wiring layer. The preferred method for manufacturing a coreless support body with a wiring layer is described below. The method for manufacturing a coreless support body with a wiring layer includes the following steps: (1) a step of preparing the copper foil with a carrier; (2) a step of forming a photoresist layer; (3) a step of forming an electroplated copper layer; (4) a step of stripping the photoresist layer; and, (5) a step of rapid etching. The method for manufacturing a coreless support body with a wiring layer including these steps is schematically shown in Figure 3 and 4 .
[0071] (1) Preparation process of copper foil with carrier
[0072] A copper foil 10 with a carrier is prepared as a support (see Figure 3(a)). As described above, the copper foil 10 with a carrier can be prepared in the form of a laminated board for a coreless support. That is, as described above, it can be provided in the form of the copper foil with a carrier itself, or it can be prepared in the form of a layer structure having an adhesive layer on the side of the carrier 12 opposite to the peeling layer 16 (i.e., the outer surface of the carrier 12) (for example, ultra-thin copper layer 18 / anti-reflection layer 17 as required / peeling layer 16 / intermediate layer 14 / carrier 12 / adhesive layer (not shown) / carrier 12 / intermediate layer 14 / peeling layer 16 / anti-reflection layer 17 as required / ultra-thin copper layer 18). It should be noted that the intermediate layer 14 can be as follows Figure 3 and 4 As shown in the figure, the two layers of the adhesion metal layer 14a and the peeling auxiliary layer 14b are sequentially provided from the carrier 12 side, and it is also possible to Figure 1 As shown, there is one intermediate alloy layer, which is as mentioned above.
[0073] (2) Photoresist layer formation process
[0074] A photoresist layer 20 is formed in a predetermined pattern on the surface of the ultra-thin copper layer 18 (see Figure 3 (b)). The photoresist is preferably a photosensitive film, such as a photosensitive dry film. The photoresist layer 20 can be given a predetermined wiring pattern by exposure and development. At this time, the copper foil 10 with a carrier of the present invention has an intermediate layer 14, so that it can show excellent peeling resistance to a developer (such as a sodium carbonate aqueous solution).
[0075] (3) Formation process of electroplated copper layer
[0076] The electroplated copper layer 22 is formed on the exposed surface of the ultra-thin copper layer 18 (i.e., the portion not masked by the photoresist layer 20). Figure 3 (c)). The copper electroplating is not particularly limited as long as it is performed by a known method.
[0077] (4) Photoresist stripping process
[0078] Next, the photoresist layer 20 is peeled off. As a result, Figure 4 As shown in (d) of FIG. 8 , the electroplated copper layer 22 remains in the form of a wiring pattern, and the ultra-thin copper layer 18 is exposed in a portion where the wiring pattern is not formed.
[0079] (5) Copper rapid etching process
[0080] Unnecessary portions of the ultra-thin copper layer 18 are removed by copper rapid etching to obtain a coreless support body having a wiring layer 24 (hereinafter referred to as a coreless support body 26 with a wiring layer). At this time, in the case where the copper foil 10 with a carrier has an anti-reflection layer 17, unnecessary portions of the ultra-thin copper layer 18 are removed by copper rapid etching to expose and leave the anti-reflection layer 17 (i.e., the copper rapid etching is stopped by the anti-reflection layer 17). From the perspective of avoiding excessive etching of the electroplated copper layer 22 and being able to reliably etch the exposed ultra-thin copper layer 18, it is preferred that the rapid etching solution use a sulfuric acid / hydrogen peroxide mixture, or a liquid containing at least one of sodium persulfate and potassium persulfate. In this way, as Figure 4 As shown in (e), the electroplated copper layer 22 / ultra-thin copper layer 18 remains in the form of a wiring pattern, and the anti-reflection layer 17 in the portion where the wiring pattern is not formed remains insoluble in the fast etching solution and becomes exposed on the surface. At this time, at least one metal selected from Cr, W, Ta, Ti, Ni and Mo constituting the anti-reflection layer 17 has the property of being insoluble in the copper fast etching solution, and therefore can exhibit excellent chemical resistance to the copper fast etching solution. That is, the anti-reflection layer 17 is not removed by the copper fast etching, and remains in an exposed state for the next image inspection process.
[0081] (6) Image inspection, etc. (optional process)
[0082] After the above-mentioned copper rapid etching, the following process is preferably performed: the coreless support 26 with a wiring layer (specifically, the wiring layer 24) is subjected to image inspection. The image inspection is typically performed as follows: using an optical automatic appearance inspection (AOI) device, a predetermined light is irradiated from a light source, a binary image of the wiring pattern is obtained, and the pattern matching of the binary image and the design data image is attempted, and the consistency / inconsistency between the two is evaluated. The image inspection is preferably performed while keeping the anti-reflection layer 17 exposed, if present. At this time, the aggregate of metal particles constituting the surface of the anti-reflection layer 17 presents a desired dark color due to the material and granular morphology of the metal, and the dark color brings a desired visual contrast with the wiring layer 24 composed of copper, thereby improving the recognizability in image inspection (such as automatic image inspection (AOI)).
[0083] After the above-mentioned image inspection, as required, it is preferred to carry out the following process: electronic components 28 such as chips are mounted on the coreless support 26 with wiring layers, thereby a printed circuit board can be manufactured. However, as mentioned above, after forming the wiring layer 24, the process of installing the chip is a method called the RDL-First method. According to this process, before the chip is installed, the wiring layer on the surface of the coreless support and the image inspection of each stacked wiring layer can be carried out, so that the defective part of each wiring layer can be avoided and the chip can be installed only on the good part. As a result, the RDL-First method is economically advantageous from the aspect of avoiding unnecessary use of chips, compared with the process of sequentially stacking wiring layers on the surface of the chip, i.e., the Chip-First method. At this time, when the copper foil 10 with a carrier of the present invention has an anti-reflection layer 17, the contrast between the surface of the electroplated copper layer 22 and the surface of the anti-reflection layer 17 in the image inspection can be fully obtained, and the image inspection can be performed with high precision. For example, the binary image of the wiring pattern obtained by the optical automatic appearance inspection (AOI) device becomes more accurate and vivid. In this way, in the manufacturing process of the printed circuit board (especially the RDL-First method), the wiring layer before the chip is installed can be image inspected with high precision, thereby improving the product yield. In addition, as an example of an electronic component 28 mounted on the wiring layer of the coreless support 26 as an arbitrary process, semiconductor components, chip capacitors, resistors, etc. can be cited. As examples of the way in which electronic components are mounted, flip chip mounting methods, chip bonding methods, etc. can be cited. The flip chip mounting method is a method of bonding the mounting pad of the electronic component 28 to the wiring layer 24 on the coreless support 26. Columnar electrodes (pillars), solder bumps, etc. can be formed on the mounting pad, and NCF (non-conductive film (Non-Conductive Film)) as a sealing resin film can be adhered to the surface of the wiring layer 24 of the coreless support 26 before installation. The bonding is preferably carried out using a low melting point metal such as solder, and an anisotropic conductive film, etc. can also be used. The die bonding method is a method of bonding the surface of the electronic component 28 opposite to the mounting pad surface to the wiring layer 24 on the surface of the coreless support 26. For this bonding, a paste or film of a resin composition containing a thermosetting resin and a thermally conductive inorganic filler is preferably used.
[0084] Method for manufacturing printed circuit board
[0085] The coreless support with wiring layers of the present invention can be used to manufacture printed circuit boards. A preferred method for manufacturing printed circuit boards is described below. The method for manufacturing printed circuit boards includes the following steps: (1) a manufacturing step of a coreless support with wiring layers; (2) a manufacturing step of a laminate with built-up layers; (3) a separation step of the laminate with built-up layers; and (4) a processing step of a multilayer circuit board. The method for manufacturing a printed circuit board including these steps is schematically shown in Figures 3 to 5 (in particular Figure 5 ).
[0086] (1) Process for manufacturing a coreless support body with wiring layer
[0087] The coreless support body 26 with wiring layer is manufactured by the method of the present invention. That is, the method of manufacturing a printed wiring board of the present invention includes a series of steps of the method of manufacturing a coreless support body with wiring layer, and repeated description is omitted here.
[0088] (2) Process for producing a laminate with a built-up layer
[0089] A build-up layer 30 is formed on the surface of the coreless support body 26 with wiring layers on which the wiring layers 24 are formed, so as to produce a laminated body 32 with build-up layers (see Figure 5 (g)). It should be noted that Figure 5 Detailed description of the build-up layer 30 is shown in FIG. 1 , but the structure of the build-up wiring layer is not particularly limited as long as a known structure used in a general printed wiring board is adopted.
[0090] (3) Separation process of laminated body with built-up layers
[0091] The laminated body 32 with the build-up layer is separated by the peeling layer 16 to obtain a multilayer circuit board 34 including the build-up layer 30. That is, the carrier 12, the intermediate layer 14 and the peeling layer 16 are peeled off and removed. In this separation process, physical separation, chemical separation, etc. can be used, and physical peeling is preferred. The physical separation method is a method in which the carrier 12 and the like are peeled off from the build-up layer 30 by hand, a clamp tool, a machine, etc. to separate and obtain the multilayer circuit board 34 (see Figure 5 (h)). At this time, the copper foil with a carrier 10 of the present invention has the intermediate layer 14, which can provide excellent stability for the mechanical peel strength of the carrier 12. As a result, the carrier 12 can be easily peeled off together with the intermediate layer 14 and the peeling layer 16.
[0092] (4) Processing steps of multi-layer circuit boards
[0093] The multilayer circuit board 34 is processed to obtain a printed circuit board 36 ( Figure 5(i)). At this time, when the anti-reflection layer 17 is present on the multilayer circuit board 34, the anti-reflection layer 17 is preferably removed by rapid etching. The rapid etching is preferably performed by selecting an appropriate etching solution according to the metal constituting the anti-reflection layer 17, as shown in Table 1 below. Table 1 shows representative etching solutions, but is not limited to these, and the type, concentration, temperature, etc. of the acid and ammonium salt can be appropriately changed from the conditions described in Table 1.
[0094] [Table 1]
[0095] Table 1
[0096]
[0097] By using such an etching liquid, the anti-reflection layer 17 can be selectively and rapidly etched, and therefore, the corrosion of the wiring layer 24 (which is composed of copper) exposed under the anti-reflection layer 17 can be significantly suppressed. That is, as an etching liquid for rapidly etching at least one metal selected from Cr, W, Ta, Ti, Ni and Mo constituting the anti-reflection layer 17, a highly selective etching liquid can be used, and as a result, the dissolution of copper constituting the wiring layer 24 by the etching liquid can be suppressed or avoided.
[0098] Figure 5 The printed circuit board 36 shown can be processed on the outer layer by various processes. For example, an insulating layer and a wiring layer as a built-up wiring layer can be stacked in any number of layers on the wiring layer 24 of the printed circuit board 36, or a solder resist layer can be formed on the surface of the wiring layer 24, and Ni-Au plating, OSP treatment (water-soluble pre-flux treatment, Organic Solderability Preservative) and the like can be implemented as surface treatments for the outer pads. Furthermore, columnar pillars and the like can be provided on the outer pads. In any case, the known processes used in general printed circuit boards can be appropriately added without special limitations.
[0099] Example
[0100] The present invention will be further described in detail based on the following examples.
[0101] Example 1
[0102] (1) Preparation of copper foil with carrier
[0103] like Figure 1As shown in FIG. 1 , a copper foil with a carrier 10 is produced by sequentially forming a film of a close-fitting metal layer 14a, a peeling auxiliary layer 14b, a peeling layer 16 and an ultra-thin copper layer 18 on a glass sheet as a carrier 12. The specific steps are as follows. It should be noted that the arithmetic mean roughness Ra mentioned in the following examples is a value measured by a non-contact surface shape measuring machine (NewView5032 manufactured by Zygo Co., Ltd.) in accordance with JIS B 0601-2001.
[0104] (1a) Vector preparation
[0105] A glass sheet (material: alkali-free glass, product name: OA10, manufactured by Nippon Electric Glass Co., Ltd.) having a thickness of 700 μm and a surface having an arithmetic mean roughness Ra of 0.5 nm was prepared.
[0106] The end surface of the carrier 12 was masked with a stainless steel plate, and various layers were formed by sputtering as described below.
[0107] (1b) Formation of Adhesive Metal Layer
[0108] A titanium layer having a thickness of 100 nm was formed as the adhesion metal layer 14 a on the surface of the carrier 12 by sputtering under the following apparatus and conditions.
[0109] - Equipment: Single-wafer magnetron sputtering equipment (manufactured by Tokki Corporation)
[0110] - Target: 8-inch (203.2 mm) diameter Ti target (99.999% purity)
[0111] -Ultimate vacuum degree Pu: less than 1×10 -4 Pa
[0112] -Carrier gas: Ar (flow rate: 100 sccm)
[0113] -Sputtering pressure: 0.35Pa
[0114] -Sputtering power: 2000W (6.2W / cm 2 )
[0115] -Film forming temperature: 40℃
[0116] (1c) Formation of peeling auxiliary layer
[0117] A copper layer having a thickness of 100 nm was formed as the peeling auxiliary layer 14 b on the adhesion metal layer 14 a by sputtering using the following apparatus and conditions.
[0118] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)
[0119] - Target: 8-inch (203.2 mm) diameter copper target (99.98% purity)
[0120] -Ultimate vacuum degree Pu: less than 1×10 -4 Pa
[0121] -Gas: Argon (flow rate: 100 sccm)
[0122] -Sputtering pressure: 0.35Pa
[0123] -Sputtering power: 2000W (6.2W / cm 2 )
[0124] -Film forming temperature: 40℃
[0125] (1d) Formation of peeling layer
[0126] An amorphous carbon layer having a thickness of 3 nm as the peeling layer 16 was formed on the peeling auxiliary layer 14 b by sputtering under the following apparatus and conditions.
[0127] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)
[0128] - Target: 8-inch (203.2 mm) diameter carbon target (99.999% purity)
[0129] -Ultimate vacuum degree Pu: less than 1×10 -4 Pa
[0130] -Carrier gas: Ar (flow rate: 100 sccm)
[0131] -Sputtering pressure: 0.35Pa
[0132] -Sputtering power: 100W (0.3W / cm 2 )
[0133] -Film forming temperature: 40℃
[0134] (1e) Formation of anti-reflection layer
[0135] A titanium layer having a thickness of 100 nm was formed as the antireflection layer 17 on the surface of the release layer 16 by sputtering under the following apparatus and conditions.
[0136] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)
[0137] - Target: 8-inch (203.2 mm) diameter titanium target (99.999% purity)
[0138] -Carrier gas: Ar (flow rate: 100 sccm)
[0139] -Ultimate vacuum degree Pu: less than 1×10 -4 Pa
[0140] -Sputtering pressure: 12Pa
[0141] -Sputtering power: 2000W (6.2W / cm 2 )
[0142] (1f) Formation of ultra-thin copper layer
[0143] Under the following apparatus and conditions, a 300 nm thick ultra-thin copper layer 18 was formed by sputtering on the anti-reflection layer 17. The arithmetic mean roughness (Ra) of the surface opposite to the release layer 16 (ie, the outer surface) of the obtained ultra-thin copper layer 18 was 3 nm.
[0144] - Equipment: Single wafer DC sputtering equipment (manufactured by Canon Tokki Corporation, MLS464)
[0145] - Target: 8-inch (203.2 mm) diameter copper target (99.98% purity)
[0146] -Ultimate vacuum degree Pu: less than 1×10 -4 Pa
[0147] -Carrier gas: Ar (flow rate: 100 sccm)
[0148] -Sputtering pressure: 0.35Pa
[0149] -Sputtering power: 2000W (6.2W / cm 2 )
[0150] -Film forming temperature: 40℃
[0151] (1g) Determination of composition analysis
[0152] As samples for composition analysis, the following samples were prepared respectively under the same manufacturing conditions as the manufacturing conditions of the adhesion metal layer 14a, the peeling auxiliary layer 14b, the peeling layer 16 and the anti-reflection layer 17 of the copper foil with a carrier obtained above: a sample with only the adhesion metal layer 14a formed on a glass sheet, a sample with only the peeling auxiliary layer 14b formed on a glass sheet, a sample with only the peeling layer 16 formed on a glass sheet, and a sample with only the anti-reflection layer 17 formed on a glass sheet. Composition analysis was performed on each sample as follows to understand the composition of each layer.
[0153] <Composition analysis of the adhesion metal layer, release auxiliary layer, and anti-reflection layer>
[0154] For the bonding metal layer 14a, the peeling auxiliary layer 14b and the anti-reflection layer 17, monitoring samples for surface analysis were prepared and elemental analysis was performed by TOF-SIMS (time-of-flight secondary ion mass spectrometry). The measurement was performed in a constant current mode under the condition of 800V-3mA. As a result, the compositions of the bonding metal layer 14a, the peeling auxiliary layer 14b and the anti-reflection layer 17 are shown below. Bonding metal layer 14a: Ti: 92.5 atomic%, O: 7.5 atomic%
[0155] Peeling auxiliary layer 14b: Cu: 99 atomic %, O: 1 atomic %
[0156] Anti-reflection layer 17: Ti: 99.6 atomic %, O: 0.4 atomic %
[0157] <Composition analysis of the peeling layer>
[0158] The peeling layer 16 (ie, carbon layer) was subjected to elemental analysis by XPS to measure the carbon concentration. As a result, the carbon concentration of the peeling layer 16 was 93 atomic % (C+O=100%).
[0159] <Measurement of the projected area circle equivalent diameter of the antireflection layer surface>
[0160] The sample just after the anti-reflection layer 17 is formed is sampled, and the surface of the anti-reflection layer 17 is photographed at 50,000 times by a scanning electron microscope to obtain a SEM image. The obtained SEM image is measured by image analysis of the binary image. Image analysis type particle size distribution software (Mountech Co., Ltd., Mac-VIEW) is used in the image analysis. The measurement is based on any 50 or more particles as the object, and the projected area circle equivalent diameter is measured for each particle, and the arithmetic mean value is calculated. As a result, the projected area circle equivalent diameter of the surface of the anti-reflection layer 17 is 60nm.
[0161] Example 2
[0162] In order to form a nickel layer instead of a titanium layer as the bonding metal layer 14a, the sputtering target was a nickel target (purity 99.999%). Except for this, the preparation and evaluation of the copper foil with a carrier were carried out in the same manner as in Example 1. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 was 3.7 nm. The composition of each layer except the bonding metal layer 14a is roughly the same as in Example 1. The composition of the bonding metal layer 14a is Ni: 99.5 atomic %, O: 0.5 atomic %.
[0163] Example 3
[0164] In order to form a chromium layer instead of a titanium layer as the bonding metal layer 14a, the sputtering target was a chromium target (purity 99.999%). Except for this, the preparation and evaluation of the copper foil with a carrier were carried out in the same manner as in Example 1. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 was 3.5 nm. The composition of each layer except the bonding metal layer 14a is roughly the same as in Example 1. The composition of the bonding metal layer 14a is Cr: 98.0 atomic %, O: 2.0 atomic %.
[0165] Example 4
[0166] As the carrier 12, an alumina plate (product name: A-476, manufactured by Kyocera Corporation) with a thickness of 1000 μm and an arithmetic mean roughness Ra of 0.2 μm was prepared, and the surface was treated by CMP (chemical mechanical polishing) to make the surface roughness Ra 1.0 nm. The preparation and evaluation of the copper foil with the carrier were carried out in the same manner as in Example 1. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 was 2.1 nm. The composition of each layer was substantially the same as in Example 1.
[0167] Example 5
[0168] As the carrier 12, a yttria-stabilized zirconia plate (yttria 10 wt%) (manufactured by Shinko Co., Ltd.) having a surface thickness of 500 μm and an arithmetic average roughness Ra of 1.0 nm was prepared by surface grinding, and the copper foil with a carrier was prepared and evaluated in the same manner as in Example 1. The results are shown in Table 2. It should be noted that the arithmetic average roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side to the peeling layer 16 was 2.2 nm. The composition of each layer was substantially the same as in Example 1.
[0169] Example 6 (Compare)
[0170] The preparation and evaluation of the copper foil with a carrier were carried out in the same manner as in Example 1 except that the adhesion metal layer 14a and the peeling auxiliary layer 14b were not formed. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 was 1.0 nm. The composition of each layer was substantially the same as in Example 1.
[0171] Example 7 (Compare)
[0172] In order to form an aluminum layer instead of the titanium layer as the bonding metal layer 14a, the sputtering target was an aluminum target (purity 99.999%). The preparation and evaluation of the copper foil with a carrier were carried out in the same manner as in Example 1. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 is 4.0 nm. The composition of each layer except the bonding metal layer 14a is roughly the same as in Example 1. The composition of the bonding metal layer 14a is Al: 98 atomic %, O: 2 atomic %.
[0173] Example 8 (Compare)
[0174] The preparation and evaluation of the copper foil with carrier were carried out in the same manner as in Example 1 except that the peeling auxiliary layer 14b was not formed. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side to the peeling layer 16 was 2.2 nm. The composition of each layer was substantially the same as in Example 1.
[0175] Example 9 (Compare)
[0176] The preparation and evaluation of the copper foil with carrier were carried out in the same manner as in Example 1 except that the close-contact metal layer 14a was not formed. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side to the peeling layer 16 was 3.1 nm. The composition of each layer was substantially the same as in Example 1.
[0177] Example 10 (Compare)
[0178] In order to form a nickel layer instead of the copper layer as the peeling auxiliary layer 14b, the sputtering target was a nickel target (purity 99.999%). The preparation and evaluation of the copper foil with a carrier were carried out in the same manner as in Example 1. The results are shown in Table 2. It should be noted that the arithmetic mean roughness Ra of the surface of the ultra-thin copper layer 18 on the opposite side of the peeling layer 16 was 2.5 nm. The composition of each layer except the peeling auxiliary layer 14b is roughly the same as in Example 1. The composition of the peeling auxiliary layer 14b is Ni: 99.0 atomic %, O: 1.0 atomic %.
[0179] Examples 11~13
[0180] Copper foil with carrier was prepared and evaluated in the same manner as in Example 1 except that a molybdenum layer (Example 11), a tungsten layer (Example 12) or a manganese layer (Example 13) was formed by sputtering instead of the titanium layer as the adhesion metal layer 14a.
[0181] Examples 14~24 (Examples 18 and 19 are comparative examples only)
[0182] In Example 1, the copper foil with carrier was prepared and evaluated in the same manner as in Example 1 except that an intermediate alloy layer having the composition shown in Table 3 was formed as a single layer of the intermediate layer 14 instead of the two layers of the adhesion metal layer 14a and the peeling auxiliary layer 14b. The results are shown in Table 3.
[0183] Examples 25~29
[0184] i) the adhesion metal layer 14a, the peeling auxiliary layer 14b, the anti-reflection layer 17 and the ultra-thin copper layer 18 were formed on the end surface of the carrier 12 without masking; and ii) the peeling layer 16 was formed by masking using a stainless steel plate, and the thickness of the peeling layer 16 on the end surface (end surface thickness) was changed. The copper foil with a carrier was prepared in the same manner as in Example 1. As a result, the thickness of each layer on the end surface of the carrier 12 (end surface thickness) is as follows.
[0185] - Adhesive metal layer 14a: titanium layer (end surface thickness: 35nm)
[0186] - Peeling auxiliary layer 14b: copper layer (end surface thickness: 35nm)
[0187] - Peeling layer 16: Carbon layer (various end thicknesses shown in Table 4)
[0188] - Anti-reflection layer 17: titanium layer (end thickness: 38nm)
[0189] -Ultra-thin copper layer 18: copper layer (end surface thickness: 100 nm)
[0190] Example 30
[0191] i) forming the intermediate layer 14 as the intermediate alloy layer, the antireflection layer 17 and the ultra-thin copper layer 18 on the end face of the carrier 12 without masking; and, ii) forming the peeling layer 16 by masking using a stainless steel plate, so that the thickness of the peeling layer 16 on the end face (end face thickness) is as shown below, and the copper foil with a carrier is produced in the same manner as in Example 1
[0192] -Intermediate layer 13 (intermediate alloy layer): Cu-Mn alloy layer (element ratio Cu:Mn=95:5, end surface thickness: 35nm)
[0193] - Peeling layer 16: Carbon layer (end thickness: 0nm)
[0194] - Anti-reflection layer 17: titanium layer (end thickness: 38nm)
[0195] -Ultra-thin copper layer 18: copper layer (end surface thickness: 100 nm)
[0196] Various evaluations
[0197] The copper foils with carriers of Examples 1 to 30 were subjected to various evaluations as shown below. The evaluation results are shown in Tables 2 to 4.
[0198] <Evaluation 1: Resistance of ultra-thin copper layer to peeling of developer>
[0199] The surface of the ultra-thin copper layer of each copper foil with a carrier is treated with 0.05 mol / L dilute sulfuric acid to remove the oxide film on the surface, and then washed with water and dried. Thereafter, a photosensitive dry film is adhered to the surface of the ultra-thin copper layer, and exposed and developed in a manner that gives a line / space (L / S) = 5μm / 5μm pattern. The development is carried out as follows: a 1.0 wt% sodium carbonate aqueous solution is used as a developer, and a spray method is used at 25°C for 2 minutes. The presence or degree of peeling of the ultra-thin copper layer caused by the developer penetrating the interlayer interface between the ultra-thin copper layer and the carrier (especially between the peeling layer and the bonding metal layer) after development is evaluated. The evaluation results obtained are rated according to the following criteria.
[0200] Evaluation AA: No peeling of the ultra-thin copper layer was observed.
[0201] Evaluation A: The ultra-thin copper layer peeled off with a diameter of 3 μm or less.
[0202] Evaluation B: The ultra-thin copper layer peeled off with a diameter of 50 μm or less.
[0203] Evaluation C: The ultra-thin copper layer peeled off with a size larger than 50 μm in diameter.
[0204] <Evaluation 2: Peelability of carrier-ultra-thin copper layer>
[0205] The peel strength of the copper foil with carrier was measured after reflow soldering and vacuum heat pressing as a thermal history in the following manner. After electrolytic copper plating with a thickness of 18 μm was performed on the ultra-thin copper layer 18 side of the copper foil with carrier 10, as thermal history 1, a reflow soldering (maintained at 260°C or above for 2 minutes) assuming electronic component mounting was performed, and then naturally cooled to room temperature. Then, as thermal history 2, the peel strength was measured after reflow soldering at 220°C and 30 kgf / cm 2 The pressure was pressed for 90 minutes. For the obtained copper-clad laminate, the peel strength (gf / cm) when the electroplated copper layer integrated with the ultra-thin copper layer 18 was peeled off was measured in accordance with JIS C 6481-1996. At this time, the measurement width was set to 50 mm and the measurement length was set to 20 mm. The peel strength (average value) obtained in this way was rated according to the following criteria.
[0206] Evaluation A: Peel strength is 2 to 10 gf / cm
[0207] Evaluation B: Peel strength is 1 to 30 gf / cm (excluding 2 to 10 gf / cm)
[0208] Evaluation C: Peel strength is less than 1 gf / cm or more than 30 gf / cm
[0209] <Evaluation 3: Evaluation of coating film notch at the end of coreless support body>
[0210] After electroplating copper on the coreless support used in Evaluation 1, the ultra-thin copper layer was rapidly etched with a sulfuric acid-hydrogen peroxide aqueous solution to form a coreless support with a wiring pattern. For the obtained coreless support with a wiring pattern, the maximum width (mm) of the notch of the coating (i.e., the ultra-thin copper layer and the anti-reflection layer) on the peeling layer at the end of the coreless support was measured and rated according to the following criteria. The results are shown in Tables 2 to 4.
[0211] -Evaluation AA: less than 0.1mm (optimal)
[0212] -Evaluation A: 0.1mm or more and less than 1mm (good)
[0213] -Evaluation B: 1mm or more and less than 2mm (allowable)
[0214] -Evaluation C: 2mm or more (not acceptable)
[0215] <Evaluation 4: Evaluation of fine pattern forming properties of buried wiring layer>
[0216] For the coreless support with wiring pattern obtained in Evaluation 3, prepreg and copper foil are sequentially stacked and cured to form a laminate with build-up layers. Thereafter, the laminate with build-up layers is mechanically separated by a peeling layer to obtain a multilayer circuit board containing build-up layers. Thereafter, the anti-reflection layer is rapidly etched based on the conditions shown in Table 1 above, the properties of the wiring layer buried in the build-up layer are observed, and the rating is performed according to the following criteria. The results are shown in Tables 2 and 3. The count of defective sheets with embedded wiring is as follows: 1 sheet is limited to 8 mm × 8 mm square, and the count is made so that the number of observed sheets in each example is 336 sheets. It should be noted that the defective mode is the peeling of the extremely thin copper layer, the close metal layer of the metal on the carrier side generated when the coreless support is peeled off, and the short circuit caused by the peeling of the peeling auxiliary layer.
[0217] -Evaluation AA: defective rate less than 5% (best)
[0218] -Evaluation A: The defective rate is 5% or more and less than 10% (good)
[0219] -Evaluation B: The defect rate is 10% or more and less than 20% (acceptable)
[0220] -Evaluation C: The defective rate is 20% or more and less than 50% (not acceptable)
[0221] <Evaluation 5: Evaluation of chemical solution penetration width>
[0222] A prepreg (FR-4 manufactured by Panasonic Corporation, 200 μm thick) of 100 mm × 100 mm was laminated on the coreless support with wiring pattern obtained in Evaluation 3, and the prepreg was cured to produce a printed circuit board. The obtained printed circuit board was subjected to desmear treatment using a sodium permanganate solution, and the chemical intrusion width (mm) was measured as an indicator of the amount of chemical solution intrusion.
[0223] This desmear treatment was carried out by sequentially performing the following treatments using the following treatment liquid produced by Rohm and Haas Electronic Materials Co., Ltd.
[0224] [Swelling treatment]
[0225] -Processing fluid: Circuposit MLB CONDITIONER 211-120mL / L and Circuposit Z-100mL / L
[0226] - Treatment conditions: immersion at 75°C for 5 minutes
[0227] [Permanganate treatment]
[0228] - Treatment fluid: Circuposit MLB Promoter 213A-110mL / L, and Circuposit MLB Promoter 213B-150mL / L
[0229] - Treatment conditions: immersion at 80°C for 5 minutes
[0230] [Neutralization treatment]
[0231] - Treatment fluid: Circuposit MLB Neutralizer 216-2-200mL / L
[0232] - Treatment conditions: immersion at 45°C for 5 minutes
[0233] The measured chemical solution penetration width (mm) was rated according to the following criteria. The results are shown in Tables 2 to 4.
[0234] -Evaluation AA: less than 0.1mm (optimal)
[0235] -Evaluation A: 0.1mm or more and less than 0.5mm (good)
[0236] -Evaluation B: 0.5mm or more and less than 2mm (allowable)
[0237] -Evaluation C: 2mm or more (not acceptable)
[0238] [Table 2]
[0239]
[0240] [Table 3]
[0241]
[0242] [Table 4]
[0243] Table 4
[0244]
Claims
1. A method for manufacturing a printed circuit board, comprising the following steps: A step of preparing a copper foil with a carrier as a support, wherein the copper foil with a carrier comprises: carrier, an intermediate layer disposed on the carrier, wherein the surface of the carrier side contains 1.0 at % or more of at least one metal selected from the group consisting of Ti, Cr, Mo, Mn, W and Ni, and the surface opposite to the carrier side contains 30 at % or more of Cu, a peeling layer disposed on the intermediate layer, and an anti-reflection layer disposed on the release layer, An extremely thin copper layer disposed on the anti-reflection layer; A step of forming a wiring layer on the surface of the ultra-thin copper layer to obtain a coreless support body with a wiring layer; forming a build-up layer on the surface of the coreless support body with a wiring layer on which the wiring layer is formed; A step of mounting electronic components on the coreless support with a wiring layer to obtain a laminated body; The step of separating the laminate to obtain a multilayer circuit board including a build-up layer; A process of removing the anti-reflection layer by selective etching to expose the wiring layer of the multilayer circuit board; and A step of providing an outer layer pad on the surface of the wiring layer.